Smart Hospital Network Enterprise Design for Medicine City Hospital via Packet Tracer - Jassim, mohammed (Anbar Journal of Engineering Science, 2024)
The scientific paper examined the possibility of developing an advanced healthcare management system in Iraq through the use of Cisco Packet Tracer software. The article stated that the aforementioned software has the potential to speed up network management operations and reduce expenses incurred in maintenance and repair activities. In addition, the article explained several challenges that may arise during the implementation of the smart hospital management system, including providing the required technical expertise, infrastructure provisions, and procedural measures necessary to protect the confidentiality of patient and employee information. The study confirmed that implementing an intelligent hospital management system in Iraq has the potential to improve healthcare quality, mitigate medical errors, enhance employee communication, and reduce disturbances within the hospital setting. Furthermore, this intervention is expected to enhance the efficiency of resource and inventory management and increase patients' experience and satisfaction with healthcare services. The article concludes that achieving the desired results in implementing a smart hospital management system using Cisco Packet Tracer software depends on the collaborative contributions of employees, managers, and technical professionals. This initiative is expected to enhance the hospital's ability to provide medical services of exceptional quality and effectively meet the diverse needs of patients.